Criminal networks, corruption and punishability: The case of Ancash’s Regional Government 2007-2014 - Nuñovero Cisneros, Lucía (2019)
This article discusses the possibilities of studying criminal networks as well as the relationships established between their members and the strategies and practices that characterize their actions; in particular, through the case of the former Regional Governor of Ancash, César Álvarez, who has been sentenced and continues to be prosecuted for crimes against the public administration. On the one hand, the article emphasizes the specific research required on political corruption and its relationship with organized crime as a basis for designing effective policies on the subject. The analysis of this case, as it has been approached by social scientists recently, also shows i) the need for studies on criminal careers of political leaders (their discourses, practices and networking activities), as a variant of Sutherland’s differential association theory, applicable to “white-collar” crime cases, and ii) the importance of discussing the punishability of criminal networks or associations with a temporary, opportunistic, flexible or variable nature, by which different groups (trade unions, political movements, professional groups) can come together through intermediariesproviding the basis of the recent political corruption phenomenon in Peru.